"Where the author comes in": author's figurations in the fiction of Camilo Castelo Branco (Muitas Vozes, 2022)
It is known that one of the peculiarities of Camilo Castelo Branco's fiction consists of a narration marked by the constant presence of the narrator. Even when absent from diegesis, it is an always visible presence in narrative discourse. It is our objective to describe the forms of this presence, both in diegesis and in discourse, reflecting on the literary and metaliterary meanings explored by the author.